1977
DOI: 10.1007/bf00973535
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic idiopathic acro-osteolysis with cranio-skeletal dysplasia, polycystic kidneys and glomerulonephritis A case of the hajdu-cheney syndrome

Abstract: A case of the Hajdu-Cheney syndrome in a 15 year old boy is described. The manifestations were: 1. isiopathic progressive acro-osteotions; 2. mutiple cranio-skeletal abnormalities; and 3. polycystic kidneys complicated by a rapidly progressive glomerulonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 6 publications
2
38
0
1
Order By: Relevance
“…Características menos comuns incluem a hipoacusia, sindactilia, insuficiência renal, cistos renais corticais, refluxo vésico-ureteral, alterações visuais e paralisia das cordas vocais. [3][4][5][6][7][8][9] Concluiu-se que o síndrome de Hadju-Cheney era diferente de outras formas de síndromes com acroosteólise pela presença de uma displasia esquelética generalizada e o fato de acroosteólise geralmente não estar presente no início da infância. 9 O paciente do presente relatório tinha estatura baixa, cabelos grossos, voz estridente e síndrome nefrótica, que evoluiu para insuficiência renal com necessidade de hemodiálise.…”
Section: Discussionunclassified
“…Características menos comuns incluem a hipoacusia, sindactilia, insuficiência renal, cistos renais corticais, refluxo vésico-ureteral, alterações visuais e paralisia das cordas vocais. [3][4][5][6][7][8][9] Concluiu-se que o síndrome de Hadju-Cheney era diferente de outras formas de síndromes com acroosteólise pela presença de uma displasia esquelética generalizada e o fato de acroosteólise geralmente não estar presente no início da infância. 9 O paciente do presente relatório tinha estatura baixa, cabelos grossos, voz estridente e síndrome nefrótica, que evoluiu para insuficiência renal com necessidade de hemodiálise.…”
Section: Discussionunclassified
“…Murphy et al [5] described a 44-year-old man with ADPKD who presented with the nephrotic syndrome and a marked deterioration in renal function, and was found to have focal glomerulosclerosis on open renal biopsy. Other authors have described ADPKD in conjunction with IgA nephrop athy [6], and idiopathic crescentic, rapidly progressive glo merulonephritis [7,8]. All of these cases demonstrated ei ther advanced renal failure or an accompanying increase in the rate of decline in renal function.…”
Section: Discussionmentioning
confidence: 99%
“…More significant proteinuria and the nephrotic syndrome are well recognised [1,4], but have usually been attributed to the polycystic kidney dis ease and in only a few cases investigated further [5][6][7][8]. Murphy et al [5] described a 44-year-old man with ADPKD who presented with the nephrotic syndrome and a marked deterioration in renal function, and was found to have focal glomerulosclerosis on open renal biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Rosenmann et al [7] described the case of a Hajdu-Cheney syndrome in a 15-year-old boy with idiopathic acro-osteolysis, multiple cranioskeletal progressive abnormalities, and polycystic kidneys complicated by a rapidly progressive glomerulonephri tis. Licina et al [8] reported a 69-year-old man with PKD that presented a progressive acute renal failure.…”
Section: Discussionmentioning
confidence: 99%